Disruption & change - Bailey, Mark; Faust, Bill (Henry Stewart Talks, 2021)
VUCA, How we can position ourselves towards disruption, Disruption, Innovation, Sony, Greenhousing (for ideas), Partnership, cooperation and curve jumping